Peningkatan Hasil Belajar Matematika Materi Induksi Melalui Pembelajaran Kooperatif Tipe Jigsaw Pada Siswa Kelas XI MIPA 1 MAN Bontang - Siti Hasnah (Universitas Muslim Indonesia, 2022)
Learning Mathematics through cooperative learning with the Jigsaw type in Class XI MIPA 1 MAN Bontang students. The number of students is 40 people, carried out in two cycles of 4 meetings each. The data taken is a test of learning outcomes and observations. The collected data were analyzed using quantitative and qualitative analysis. The focus of the research on seven aspects, namely: the average value of Mathematics learning outcomes, student attendance in Mathematics lessons, students who ask questions, students who appear to solve problems, students who collect homework assignments on time, Students who answer teacher questions, Students who helps his friend solve the problem.From the results of this study it can be concluded that by applying a contextual approach with a jig saw type learning model, the results of Mathematics learning for Class XI MIPA 1 MAN Bontang students become effective.